Clinical Results and Biomarker Analyses of Axitinib and TRC105 versus Axitinib Alone in Patients with Advanced or Metastatic Renal Cell Carcinoma (TRAXAR). (29th April 2021) - Choueiri, Toni K.; Zakharia, Yousef; Pal, Sumanta; Kocsis, Judit; Pachynski, Russell; Poprach, Alexandr; Nixon, Andrew B.; Liu, Yingmiao; Starr, Mark; Lyu, Jing; Owzar, Kouros; deShazo, Mollie; et al.
Abstract: Lessons Learned: The combination of carotuximab with axitinib did not provide a benefit over axitinib monotherapy in patients with metastatic clear cell renal cell carcinoma who had previously progressed on one or more vascular endothelial growth factor (VEGF)-targeted therapies. Exploratory evaluation of pretreatment circulating biomarkers suggested the combination might benefit patients who have low baseline VEGF levels. Background: Endoglin is an angiogenic receptor expressed on proliferating tumor vessels and renal cell carcinoma (RCC) stem cells that is implicated as a mechanism of resistance to vascular endothelial growth factor receptor (VEGFR) inhibitors. This study evaluated an antiendoglin monoclonal antibody (carotuximab, TRC105) combined with axitinib in patients with advanced or metastatic clear cell renal cell carcinoma (mccRCC) who had progressed following one or more prior VEGF inhibitors. Methods: TRAXAR was a multicenter, international randomized 1:1 (stratified by ECOG, 0 vs. 1), phase II study of carotuximab combined with axitinib versus axitinib alone in mccRCC patients who had progressed following one or more prior VEGF inhibitors. The primary endpoint was progression-free survival (PFS) assessed by independent central review (ICR) per RECIST 1.1 Results: A total of 150 patients were randomized. The combination therapy resulted in shorter median PFS by RECIST 1.1 than axitinib monotherapy (6.7 vs. 11.4 months). The combination was tolerated similarly to axitinib monotherapy, and there were no treatment related deaths. Exploratory evaluation of pretreatment circulating biomarkers suggested the combination might benefit patients who have low baseline VEGF levels. Conclusion: The combination of carotuximab with axitinib did not demonstrate additional efficacy over single agent axitinib in patients with mccRCC who progressed following one or more prior VEGF inhibitor treatment.